Mobile Phone Rewards to Improve Qur’anic Memorization at Ma’had Aly IHBS - Adzima, Fauzan; Hadi, Sofian; Marina, Silvia; Alfian Mubarok (Journal of Islamic Civilization, 2025)
This study explores the effectiveness of a reward system, in the form of granting mobile phone access, as a strategy to enhance motivation and memorization outcomes among students in the tahfiz program at Ma’had Aly Ibnu Hajar Boarding School (IHBS). The policy was introduced in a limited and regulated format during the 2024–2025 academic year, marking a significant shift in the pesantren tradition, which typically restricts mobile phone use. Employing a descriptive quantitative approach enriched with qualitative insights, data were collected through open-ended questionnaires administered to 21 students from the third and fourth semesters who had experienced the tahfiz process both before and after the reward system was introduced. The findings indicate that 80% of the respondents experienced an increase in motivation and memorization output, reporting improved consistency and enthusiasm in achieving targets. Nonetheless, a few students raised concerns regarding the sincerity and purity of their intentions, suggesting that extrinsic rewards may affect spiritual focus if not properly managed. The study concludes that mobile phone–based rewards, when implemented under strict supervision and embedded within a spiritually grounded educational environment, can serve as an effective motivational tool in tahfiz institutions. These findings offer practical insights for pesantren seeking culturally sensitive and innovative strategies to support students’ long-term commitment to Quranic memorization.